Environmental impact assessment : a guide to procedures (Thomas Telford, 2000)
This guide explains how EC requirements for environmental impact assessment have been incorporated into procedures in the UK. It revises the booklet Environmental Assessment: A guide to the procedures, published in 1989, to take account of the requirements of the Directive 97/11/EC, which was adopted on 3 March 1997 and came into force on 14 March 1999. Parts 1 and 2 of the guide explain the procedures that apply to projects that fall within the scope of the Directive and require planning permission in England and Wales. They also give general advise and guidance.
Keywords: Environmental impact analysis -- Great Britain -- Handbooks, manuals, etc.; Great Britain.; elektronické knihy; electronic books